Long‐distance dispersal in the short‐distance dispersing house sparrow ( Passer domesticus ) - Ranke, PS; Pepke, ML; Søraker, JS; David, G; Araya‐Ajoy, YG; Wright, J; Nafstad, ÅM; Rønning, B; Pärn, H; Ringsby, TH; Jensen, H; Sæther, B (Wiley Open Access, 2024)
The house sparrow (Passer domesticus) is a small passerine known to be highly sedentary. Throughout a 30‐year capture–mark–recapture study, we have obtained occasional reports of recoveries far outside our main metapopulation study system, documenting unusually long dispersal distances. Our records constitute the highest occurrence of long‐distance dispersal events recorded for this species in Scandinavia. Such long‐distance dispersals radically change the predicted distribution of dispersal distances and connectedness for our study metapopulation. Moreover, it reveals a much greater potential for colonization than formerly recorded for the house sparrow, which is an invasive species across four continents. These rare and occasional long‐distance dispersal events are challenging to document but may have important implications for the genetic composition of small and isolated populations and for our understanding of dispersal ecology and evolution.